HIV/AIDS Stigma and Discrimination in Pakistan: A Qualitative Study - Shafee Ullah; Ulhaq, Fiaz; Basit, Abdul; Imtiaz, Fazeela; Noreen, Atika; Elahi, Ahsan; Attiq-Ur-Rehman (Indus Journal of Bioscience Research, 2024)
HIV/AIDS remains a major public health issue globally, yet individuals living with HIV/AIDS (PLHIV) face not only health challenges but also significant social stigma and discrimination. In Pakistan, where cultural, religious, and socio-economic factors intersect, the stigma surrounding HIV/AIDS is particularly complex and entrenched. The study reveals that HIV/AIDS stigma in Pakistan is predominantly fueled by misconceptions about the disease's transmission, moral judgment against behaviors associated with HIV acquisition, and fear of contagion. Key themes emerging from the data include isolation within family and social circles, emotional distress, barriers to healthcare, and discriminatory practices in employment and housing. Participants frequently reported feeling dehumanized and ostracized, leading to profound psychological effects such as depression, anxiety, and a reluctance to disclose their status or seek support. These findings highlight the urgent need for culturally sensitive stigma-reduction interventions, such as community education programs, training for healthcare providers, and stronger policies protecting the rights of PLHIV in Pakistan. By addressing the deeply rooted stigma and discrimination against PLHIV, policymakers and practitioners can foster a more supportive and inclusive environment, ultimately improving the quality of life for those affected and enhancing the country’s public health response to HIV/AIDS. This study contributes to the limited body of literature on HIV/AIDS stigma in South Asia and underscores the importance of a nuanced understanding of social attitudes toward HIV/AIDS in Pakistan.